Impact of Community-Led Total Sanitation on the Sustainability of Open Defecation-Free Communities and Sanitation Infrastructure in Ona Ara Local Government Area, Oyo State - Kabiru, Adeola, OLADEJO; Henry, Olawale SAWYERR; Ahmed, Olanrewaju SAKARIYAU; Grace, Kehinde ADEBAYO (FUDMA Journal of Sciences, 2025)
Open defecation remains a major public health and environmental challenge in Nigeria, affecting millions of people across rural and urban communities. The problem is largely driven by inadequate sanitation infrastructure, poverty, and entrenched cultural practices. This study assessed the post-implementation impact of Community-Led Total Sanitation (CLTS) in Ona Ara Local Government Area, Ibadan, Oyo State, Nigeria, focusing on the sustainability of Open Defecation-Free (ODF) status and the development of sanitation infrastructure. A cross-sectional survey involving 150 respondents was conducted using structured questionnaires to gather data on sanitation practices and latrine ownership. The findings revealed that 96.0% of respondents no longer practice open defecation, and 74.7% of communities have maintained their ODF status. Latrine ownership was notably high at 98.0%, reflecting substantial improvement in sanitation infrastructure. However, 75.3% of respondents reported challenges in sustaining ODF status, attributed mainly to lack of awareness (30%), poor maintenance (25%), and cultural resistance (24.7%). The study concludes that CLTS has significantly improved sanitation outcomes in Ona Ara LGA by promoting latrine construction and reducing open defecation. Nevertheless, sustaining ODF status requires continued community sensitization, improved facility maintenance, and supportive policy implementation.
Keywords: Community-Led Total Sanitation (CLTS); Open Defecation; Open Defecation-Free (ODF); Sanitation; Sanitation infrastructure